Recent Advances on Multivalent Carbon Nanoform-Based Glycoconjugates - Ramos-Soriano, Javier; Ghirardello, Mattia; Galan, M. C. (Current Medicinal Chemistry, 2022)
Multivalent carbohydrate-mediated interactions are key to many biological processes including disease mechanisms. In order to study these important glycan-mediated interactions at a molecular level, carbon nanoforms such as fullerenes, carbon nanotubes or graphene and their derivatives have been identified as promising biocompatible scaffolds that can mimic the multivalent presentation of biologically relevant glycans. In this mini-review, we will summarize the most relevant examples of the last few years in the context of their applications.
Keywords: nanomedicine